Implementation of Sustainable Finance and Good Corporate Governance: Profitability Perspective of State-Owned Banks Listed - Triyono Adi Tristanto; Nugraha Nugraha; Maya Sari; Abdul Muhaimin Elyusufi (Budapest International Research and Critics University, 2022)
The research method uses multiple linear regression analysis to test the effect of the independent variable on the dependent variable with purposive sampling technique using several criteria such as the availability of sustainability reports and annual reports on listed state-owned banks that upload sustainability reports and annual reports for at least 5 (five) years of publication and have positive profitability ratios. The results of the study indicate that the variables of Economic Performance and the Audit Committee have an influence onProfitability (ROE) of state-owned banks with a significance value of 0.029 and respectively 0.016 smaller than = 0.05. Temporary VariableSocial Performance, Environmental Performance, K.INSTI and KOM.INDI has no effect on Profitability (ROE) of state-owned banks. Two variables that have an influence on the profitability (ROE) of state-owned banks indicate that the implementation of sustainable finance proxied by economic performance can encourage the company's reputation in building stakeholder trust and the implementation of good corporate governance through the role of the audit committee will help improve corporate control for increase company profitability.